Comparison and relationship of returns: Case of technology and healthcare sectors - Berlianta Ginting; Eirene Flandrina Gamani; Fadisti Prameswari Hursan; Gabriela Ester Olivia Rarung (Yayasan Widyantara Nawasena Raharja, 2022)
The Covid-19 pandemic can have both positive and negative impacts. The technology sector and the health sector are sectors that have experienced significant increases since the pandemic. The objective of this study is to examine the comparison and relationship between firms engaged in the technology sector and the health sector in Indonesia. The results of the analysis over the period 17 June 2021 to 3 June 2022 show that the returns of both sectors are not significantly different. Empirically, this study proves that stock returns of both sectors are not unidirectional and have an insignificant relationship.